Significance of Nerve Plane for Inferior Mesenteric Plexus Preservation in Laparoscopic Rectal Cancer Surgery - Li, Kai; Zeng, Junjie; Pang, Pengcheng; Cheng, Hua; He, Xiaobo; Cao, Fengyu; Luo, Qiang; Tong, Shilun; Zheng, Yongbin (Frontiers in Oncology, 2022)
Background: Station 253 node dissection with high ligation of the inferior mesenteric artery (IMA) is difficult to perform without damage to the surrounding autonomic nerve plexuses. This study aimed to investigate the significance of the nerve plane for inferior mesenteric plexus (IMP) preservation in laparoscopic rectal cancer surgery. Methods: 56 consecutive rectal patients underwent laparoscopic en bloc station 253 node dissection with high ligation of the IMA. Station 253 nodes were divided into the extra- and intra-nerve plane station 253 nodes for further H&E staining and immunohistochemical analysis. Based on IMP nerve plane-based evidence and histopathological results, a novel nerve-sparing technique, IMP nerve plane-oriented, was proposed and performed in 68 rectal cancer patients. Urinary and sexual functions in all patients were evaluated at 6 months postoperatively. Results: Lymph node metastasis was not found, but abundant nerve bundles containing gangliocytes were observed in extra-nerve plane station 253 nodes. The nerve plane was identified intraoperatively and then confirmed by both postoperative gross specimen evaluation and histopathological analysis. The novel nerve-sparing technique (IMP nerve plane-oriented) was successfully performed with no postoperative complications, and the operated patients had improved postoperative urinary and sexual functions. Conclusion: The nerve plane is helpful for IMP preservation and station 253 node dissection. This novel nerve-sparing technique of nerve plane-oriented is technically feasible and safe, which could result in faster recovery of urinary and sexual functions.